Winter climate and non motorised travel modes – a case study in Kiruna Sweden : Results from a travel survey in North of Sweden - Ebrahimabadi, Saeed; Johansson, Charlotta; Öberg, Maria; Nilsson, Kristina L. (Luleå tekniska universitet, Arkitektur och vatten, 2011)
Godkänd; 2011; 20111222 (andbra)